2021
DOI: 10.1101/2021.07.10.21260232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 variants of concern exhibit reduced sensitivity to live-virus neutralization in sera from CoronaVac vaccinees and naturally infected COVID-19 patients

Abstract: Recent surges in SARS-CoV-2 variants of concern (VOCs) call for the need to evaluate levels of vaccine- and infection- induced SARS-CoV-2 neutralizing antibodies (NAbs). CoronaVac (Sinovac Biotech, Beijing, China) is currently being used for mass vaccination in Thailand as well as other low-income countries. Three VOCs currently circulating within Thailand include the B.1.1.7 (Alpha), B.1.351 (Beta), and B.1.617.2 (Delta) strains. We assessed NAb potency against the prototypic strain containing the original sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
5
5
0
Order By: Relevance
“…In non-cancer population, inconsistent results have been reported regarding the length of persistence of both SARS-CoV-2-specific IgG and NAb over time, 20,[28][29][30][31] thus it is challenging to relate our data to those prior reports. In line with data for non-cancer SARS-CoV-2 convalescent patients 32 , we found that neutralising activity against Alpha, Beta, and Delta VOCs was decreased. This raises concerns about the ability of natural immunity to one variant to protect against other VOCs.…”
Section: Discussionsupporting
confidence: 89%
“…In non-cancer population, inconsistent results have been reported regarding the length of persistence of both SARS-CoV-2-specific IgG and NAb over time, 20,[28][29][30][31] thus it is challenging to relate our data to those prior reports. In line with data for non-cancer SARS-CoV-2 convalescent patients 32 , we found that neutralising activity against Alpha, Beta, and Delta VOCs was decreased. This raises concerns about the ability of natural immunity to one variant to protect against other VOCs.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, antibody levels of the I/I schedule at 4 wks were lower than natural infection 2021.This agreement with a prior study that S1-RBD-binding IgG titer of natural infection 2021 was higher than homologous CoronaVac vaccination 8 .…”
Section: Discussionsupporting
confidence: 91%
“…This is compatible with a previous study utilizing a pseudovirus neutralization assay, serum from CoronaVac vaccinees collected 14 days following the second dose of the vaccine presented higher Beta resistance to neutralization than Alpha 16 . Moreover, this Nab level at 2wks against all VOCs decreased significantly compared to WT correlate with study 8 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It has been reported that the variant Delta was more resistant to neutralization by some monoclonal antibodies toward RBD and N-terminal domain of SARS-CoV-2 as well as by two doses of Pfizer or AstraZeneca vaccine [ 5 ]. A preprint result from Thailand suggested a similar finding, in which CoronaVac-vaccinated subjects had a much reduced neutralizing capacity against the variant Delta [ 6 ]. As two doses of CoronaVac only induced relatively low titers of anti-SARS-CoV-2 RBD antibodies, it is likely that CoronaVac-vaccinated individuals will require a booster.…”
mentioning
confidence: 87%